1993
DOI: 10.1016/0014-5793(93)81021-q
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of apo‐glycolate oxidase

Abstract: The crystal structure of the apoform of the a&barrel enzyme glycoiate oxidase has been determined to 2.6 A resolution. Removal of the tightly bound cofactor FMN has a very strong influence on the protein structure; it is converted into a very flexible state, verging on a molten globule type of structure. The asymmetric unit contains two subunits with different conformations to each other and to the halo-enzyme. The secondary structures are preserved, but their mutual arrangement has changed to some extent intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In such cases conformational changes induced by binding of the hydride acceptor are well documented (27)(28)(29)(30). In a striking example of this, the structure of glycolate oxidase verges on a molten globule-like state in the absence of the co-factor, FMN (30). Binding of the co-factor induces widespread structural reorganization and stabilization, whereupon the enzyme active site residues are oriented optimally for catalysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases conformational changes induced by binding of the hydride acceptor are well documented (27)(28)(29)(30). In a striking example of this, the structure of glycolate oxidase verges on a molten globule-like state in the absence of the co-factor, FMN (30). Binding of the co-factor induces widespread structural reorganization and stabilization, whereupon the enzyme active site residues are oriented optimally for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…In most other dehydrogenases substrate binding is either random or the hydride acceptor binds first (26). This binding often induces a large conformational change that prepares the enzyme for the catalytic events (27)(28)(29)(30). In the case of IMPDH, catalysis proceeds via an ordered bi-bi kinetic mechanism wherein IMP (the hydride donor) binds first and NAD ϩ binds second.…”
mentioning
confidence: 99%
“…18 In ThDP-dependent enzymes, it has been reported that TK shows a disorder -order transition of two loop regions upon binding of the cofactors ThDP and Ca 2þ . 16 However, it is unclear whether or not this is a common feature of ThDP-dependent enzymes, since structures of other ThDP-dependent enzymes in both apo and holo-forms have not been elucidated.…”
Section: Disorder-order Transition Upon Binding Of the Cofactors Thdpmentioning
confidence: 99%
“…Flavoproteins represent one of the major groups of cofactordependent enzymes (1,2). However, data on the molecular process of FAD or FMN binding are scarce, while only a limited number of flavoprotein structures in the apo form are known (3)(4)(5). A striking example of the importance of efficient FAD binding was recently shown for methylenetetrahydrofolate reductase (6).…”
mentioning
confidence: 99%